Decay properties of a class of doubly charged Higgs bosons - Tonasse, M. D. [UNESP] (Elsevier B.V., 2012)
We study the leptonic decays of a doubly charged Higgs bosons class which is predicted by a model based on the SU(3)(C) circle times SU(2)(L) circle times U(1)(N) electroweak gauge symmetry. In contrast to other models, decays into tau(+/-)tau(+/-) are largely dominant (99.5% or more). Coupling of these scalars to two standard charged gauge bosons are either zero or very suppressed. Couplings to two different flavor of charged leptons do not occur. Some coupling features imposed by symmetry and representation content lead to simple relationships between decay rates and doubly charged Higgs masses. Some of the parameters depend only on the decay widths and on the charged lepton masses. In order to clarify the relevance of our results, some aspects of this model are compared with the Higgs triplet model. (C) 2012 Elsevier B.V. All rights reserved.